TCM targets ferroptosis: potential treatments for cancer - Qin, Liwen; Zhong, Yuhan; Li, Yi; Yang, Yongfeng (Frontiers in Pharmacology, 2024)
Ferroptosis is caused by the accumulation of cellular reactive oxygen species that exceed the antioxidant load that glutathione (GSH) and phospholipid hydroperoxidases with GSH-based substrates can carry When the antioxidant capacity of cells is reduced, lipid reactive oxygen species accumulate, which can cause oxidative death. Ferroptosis, an iron-dependent regulatory necrosis pathway, has emerged as a new modality of cell death that is strongly associated with cancer. Surgery, chemotherapy and radiotherapy are the main methods of cancer treatment. However, resistance to these mainstream anticancer drugs and strong toxic side effects have forced the development of alternative treatments with high efficiency and low toxicity. In recent years, an increasing number of studies have shown that traditional Chinese medicines (TCMs), especially herbs or herbal extracts, can inhibit tumor cell growth and metastasis by inducing ferroptosis, suggesting that they could be promising agents for cancer treatment. This article reviews the current research progress on the antitumor effects of TCMs through the induction of ferroptosis. The aim of these studies was to elucidate the potential mechanisms of targeting ferroptosis in cancer, and the findings could lead to new directions and reference values for developing better cancer treatment strategies.